1978
DOI: 10.1083/jcb.77.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Localization of D-amino acid oxidase on the cell surface of human polymorphonuclear leukocytes

Abstract: The ultrastructural localization of o-amino acid oxidase (DAO) was studied cytochemically by detecting sites of hydrogen peroxide production in human polymorphonuclear leukocytes (PMNs). Reaction product, which forms when cerous ions react with HzO2 to form an electron-dense precipitate, was demonstrated on the cell surface and within the phagosomes of phagocytically stimulated cells when D-amino acids were provided as substrate. Resting cells showed only slight activity. The competitive inhibitor O,L-2-hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…This visible product showed high contrast in comparison with other histochemical methods including the tetrazolium method (12,16,27,38,40,46,47) and the previous coupled-peroxidation method (16) . The cerium method (3,37,41,42) is useful for electron microscopic demonstration of the oxidase activity, but is inapplicable to light microscopy because of the nonvisible product.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This visible product showed high contrast in comparison with other histochemical methods including the tetrazolium method (12,16,27,38,40,46,47) and the previous coupled-peroxidation method (16) . The cerium method (3,37,41,42) is useful for electron microscopic demonstration of the oxidase activity, but is inapplicable to light microscopy because of the nonvisible product.…”
Section: Discussionmentioning
confidence: 99%
“…20) . They are based on three general means of detection : the reduction of tetrazolium (12,16,27,38,40,46,47) or ferricyanide (37) during oxidation of the substrate; the coupled peroxidation methods for hydrogen peroxide detection (14,16,(42)(43)(44) or the direct detection of hydrogen peroxide with cerous chloride (3,37,41,42) ; and immunocytochemical methods (39,43). However, it seems that they are not practical as to sensitivity or simplicity.…”
mentioning
confidence: 99%
“…Robinson et al reported that DAO is located on the cell surface and DAO is internalized with foreign objects, such as bacteria (26). Reports that purified porcine DAO has antibacterial activity against Escherichia coli in vitro and that its activity was enhanced by addition of D-amino acids, as well as by binding of DAO to bacterial cell walls, have appeared in the literature (10,29).…”
mentioning
confidence: 99%
“…On this viewpoint attempts were reported, introducing cadmium, strontioum, barium, and cerium (52). Of these metals, cerium is shown to be excellent in the precise localization of reaction product at the ultrastructural level (45)(46)(47)(48). Its disadvantage is that it is rather difficult for developing color in light microscopy (41 Unlike ACase, which is considered to be totally particulate, the major portion of GCase appears to reside in the soluble fraction after the homogenization of most tissues, but there was still some detectable activity in the particulate fraction (39).…”
mentioning
confidence: 99%